FRI0474 IMMUNE CHECKPOINT INHIBITOR-INDUCED MUSCULOSKELETAL MANIFESTATIONS. A SYSTEMATIC REVIEW. (2nd June 2020) - Angelopoulou, F.; Antonopoulos, I.; Bogdanos, D.; Dimitroulas, T.; Sakkas, L.; Daoussis, D.
Abstract : Background: Immune checkpoint inhibitors (ICI) are potent anti-cancer drugs that associate with a wide range of immune related adverse events (Ir-AE), including musculoskeletal manifestations. Objectives: We performed a systematic literature review of ICI-induced musculoskeletal manifestations aiming at exploring the following: 1) the prevalence of these manifestations and the time from first ICI administration to symptom onset, 2) the main clinical phenotypes and the type of treatment required to control symptoms (steroids/DMARDs), 3) the type of ICI (CTLA-4 vs PD-1/PD-L1 inhibitors) mostly associated with Ir-AE, 4) the percentage of patients with positive auto-antibodies and family history of autoimmune disease, 5) the percentage of patients requiring permanent ICI discontinuation due to musculoskeletal Ir-AE, 6) the association between musculoskeletal Ir-AE and oncologic response and 7) the risk of flare in patients with pre-existing autoimmune disease (PAD). Methods: An electronic (PubMed) search was performed aiming at identifying all studies reporting musculoskeletal Ir-AE. Results: We identified 3 prospective studies, 17 retrospective studies and 4 case series reporting 363 patients in total. Combined data from all 3 prospective studies provide a prevalence rate of 6.13%. Most patients were males (59.68%) and the vast majority (73%) were on programmed death-1 (PD-1)/programmed death ligand-1 (PD-L1) inhibitors. Most studies report a median time of ≤ 12 weeks from first ICI administration to symptom onset. The main clinical phenotypes reported were: a) inflammatory arthritis (57.57%), b) myositis (14.04%) and c) polymyalgia rheumatica (PMR) (12.12%). A total of 256 patients required steroids (70.52%) and 67 patients (18.45%) were treated with DMARDs. From the 363 patients reported in total, 265 (73%) were treated with PD-1/PD-L1 inhibitors in sharp contrast to only 11 (3.03%) with CTLA4 inhibitors with the rest patients receiving combination immunotherapy Positive auto-antibodies and family history of any autoimmune disease were present in 18.48% and 19.04% of cases, respectively. Only a few patients (19%) had to discontinue treatment due to musculoskeletal Ir-AE. Two prospective studies show that significantly more patients with musculoskeletal Ir-AE exhibit a favorable oncologic response compared to patients not exhibiting such manifestations whereas retrospective studies show that 77.22% of patients with musculoskeletal Ir-AE have a good tumor response. Conclusion: One out of 15 patients treated with ICI will develop musculoskeletal Ir-AE; in most cases the severity of these manifestations is mild/moderate and usually ICI is continued. Rheumatologists should familiarize themselves with this new clinical entity and develop relevant therapeutic algorithms. Disclosure of Interests: None declared